2010
DOI: 10.1097/adm.0b013e3181b18782
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors for Marijuana Use Among Veterans Affairs Patients

Abstract: Objectives Cannabis is the most widely used drug in the United States, and its use carries negative health consequences; however, universal screening for cannabis use is cumbersome. If data commonly collected in the primary care setting (eg, use of alcohol, smoking status, and depression symptoms) could predict cannabis use, then providers can implement targeted marijuana screening in high-risk groups. Methods We reviewed Behavioral Health Laboratory data collected between 2003 and 2006 from 5512 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
0
19
3
Order By: Relevance
“…Past six month prevalence rates in the current study (14.6%) were slightly higher than the past year prevalence found in previous research (11.5%; Goldman et al, 2010), which may be attributable to differences in the sample composition, including the exclusion of female participants, as well as the possibility that individuals presenting to a PTSD specialty clinic may show more severe anxiety and mood symptoms than those being referred from primary care. Further, a large percentage (27.6%) of participants who reported cannabis use in the present study reported daily use.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Past six month prevalence rates in the current study (14.6%) were slightly higher than the past year prevalence found in previous research (11.5%; Goldman et al, 2010), which may be attributable to differences in the sample composition, including the exclusion of female participants, as well as the possibility that individuals presenting to a PTSD specialty clinic may show more severe anxiety and mood symptoms than those being referred from primary care. Further, a large percentage (27.6%) of participants who reported cannabis use in the present study reported daily use.…”
Section: Discussioncontrasting
confidence: 87%
“…The purpose of the present study was to extend Goldman and colleagues’ (2010) findings by examining the prevalence of cannabis use and its psychological and functional correlates among a large sample of veterans seeking treatment at a VA PTSD specialty clinic.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, heavy cannabis use (i.e., cannabis use on 20 or more days during the past month) increased by nearly 60% in the U.S. from 2007 to 2013 (SAMHSA, 2014). Such findings are important because cannabis use has been associated with a wide range of health problems (e.g., Goldman et al, 2010; Joshi et al, 2014). To date, however, there has been only limited attention paid to the relationship between cannabis use and suicidal behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Prior studies have found a number of risk factors and correlates for cannabis use in general, including male gender, psychiatric conditions (4, 5) and other substance use (6). Nonetheless, there has only been limited research examining differences between those who use cannabis for medical versus recreational purposes.…”
Section: Introductionmentioning
confidence: 99%